2000
DOI: 10.1177/155005940003100403
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Abnormal EEG Activity in Brain Infarctions

Abstract: EEGs from 16 patients with stroke in three different stages of evolution were recorded. EEG sources were calculated every 0.39 Hz by frequency domain VARETA. The main source was within the delta band in 2 out of 4 chronic patients, and in 67% of the patients in the acute or subacute stages when edema (cytotoxic or vasogenic) was present. Moreover, all patients showed abnormal activity in the theta band. Sources of abnormal activity in cortical or corticosubcortical infarcts were located in the cortex, surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“…Prior studies that showed deviant EEG activation patterns in stroke patients constantly reported abnormalities in the delta frequency range (Giaquinto et al 1994; Finnigan et al 2007, 2008; Finnigan and van Putten 2013; Fernandez-Bouzas et al 2000; Claassen et al 2004; Sheorajpanday et al 2011; Tecchio et al 2006). The majority of prior studies also demonstrated pathological alpha activity after stroke (Giaquinto et al 1994; Finnigan et al 2007; Finnigan and van Putten 2013; Sheorajpanday et al 2011; Claassen et al 2004; Tecchio et al 2006; Fernandez-Bouzas et al 2000). However, a few studies also reported on pathological theta or beta activity after stroke, which could not be observed in the present investigation (Giaquinto et al 1994; Tecchio et al 2006, 2007; Finnigan and van Putten 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies that showed deviant EEG activation patterns in stroke patients constantly reported abnormalities in the delta frequency range (Giaquinto et al 1994; Finnigan et al 2007, 2008; Finnigan and van Putten 2013; Fernandez-Bouzas et al 2000; Claassen et al 2004; Sheorajpanday et al 2011; Tecchio et al 2006). The majority of prior studies also demonstrated pathological alpha activity after stroke (Giaquinto et al 1994; Finnigan et al 2007; Finnigan and van Putten 2013; Sheorajpanday et al 2011; Claassen et al 2004; Tecchio et al 2006; Fernandez-Bouzas et al 2000). However, a few studies also reported on pathological theta or beta activity after stroke, which could not be observed in the present investigation (Giaquinto et al 1994; Tecchio et al 2006, 2007; Finnigan and van Putten 2013).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, source EEG spectral analysis has a different objective: the estimation of S(x) the source cross-spectrum. This procedure, called frequency-domain VARETA, has been applied to the localization of brain tumors, infarcts and other type of cerebral lesions with great accuracy, including subcortical lesions , 2000Prichep et al, 2001). …”
Section: Eeg Source Spectral Analysismentioning
confidence: 99%
“…Many previous studies suggested that slow wave activity in the delta frequency range is highly typical in ischemic stroke [14, 16, 22, 24, 4248] (Butz et al [16], 0.5–3 Hz; Sakamoto et al [22, 24], 0.3–4 Hz; Nuwer et al [43], 0.1–4 Hz; Nagata et al [44], 0.4–4 Hz; Nagata et al [45], 2.0–3.8 Hz; Finnigan et al [47], 1–4 Hz; Burghaus et al [48], <1 Hz). Furthermore, delta activity has the strongest correlation with regional cerebral blood flow in patients with supratentorial and unilateral cerebral infarction [4446].…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalography (EEG), which is a method of electrophysiological examination, can also demonstrate the area of reversible cerebral ischemia (ischemic penumbra) as slow waves [1214]. However, in the age of MRI, EEG has minimal clinical applications for evaluating cerebral ischemia because it has markedly low spatial resolution, which is due to the presence of the scalp, skull, and cerebrospinal fluid between the brain and the electrodes.…”
Section: Introductionmentioning
confidence: 99%